2017
DOI: 10.1111/ecog.02683
|View full text |Cite
|
Sign up to set email alerts
|

Do cryptic species matter in macroecology? Sequencing European groundwater crustaceans yields smaller ranges but does not challenge biodiversity determinants

Abstract: Ecologists increasingly rely on molecular delimitation methods (MMs) to identify species boundaries, thereby potentially increasing the number of putative species because of the presence of morphologically cryptic species. It has been argued that cryptic species could challenge our understanding of what determine large‐scale biodiversity patterns which have traditionally been documented from morphology alone. Here, we used morphology and three MMs to derive four different sets of putative species among the Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 69 publications
3
91
1
Order By: Relevance
“…While we had genetic data for the majority of species, we are missing these data at the population level, and would expect that at least some of the nominal species contain multiple cryptic species. Cryptic species are a common phenomenon in Niphargus (Lefébure et al , Trontelj et al , Meleg et al , Delić et al , b, Eme et al ) and may be broadly sympatric or even co‐occurring (Fišer et al 2015b, Delić et al ). Cryptic species may increase the complexity of local communities and underestimate taxonomic structure, possibly affecting the conclusions (Fišer et al ).…”
Section: Discussionmentioning
confidence: 99%
“…While we had genetic data for the majority of species, we are missing these data at the population level, and would expect that at least some of the nominal species contain multiple cryptic species. Cryptic species are a common phenomenon in Niphargus (Lefébure et al , Trontelj et al , Meleg et al , Delić et al , b, Eme et al ) and may be broadly sympatric or even co‐occurring (Fišer et al 2015b, Delić et al ). Cryptic species may increase the complexity of local communities and underestimate taxonomic structure, possibly affecting the conclusions (Fišer et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Use of different molecular markers and species delineation methods revealed conflicting results about the number of species. Alternative species delimitations suggested by different methods were not in conflict with each other, but differed in the degree of splitting; distance methods typically turned to be more conservative (Copilaş‐Ciocianu & Petrusek, ; Delić, Trontelj, Rendoš, & Fišer, ; Delić, Švara, et al., ; Eme et al., ; Katouzian et al., ; Weiss et al., ). In such cases, authors either provided a rough estimate of species number (Copilaş‐Ciocianu & Petrusek, ; Weiss et al., ), opted for a particular species hypothesis by ranking the efficiency of different methods (e.g., conservative ABGD was preferred over PTP and bGMYC; Katouzian et al., ), reconsidered the results within spatial context (presence of syntopy (Delić, Trontelj, et al., )) or drew on other studies to justify the choice of a particular threshold value.…”
Section: Taxonomic Practices In Delimiting Cryptic Speciesmentioning
confidence: 99%
“…The authors found that cryptic species were homogeneously distributed among taxa and regions and concluded “that cryptic metazoan diversity can be treated as random error in biodiversity assessments.” Their meta‐analysis was later criticized for several methodological problems (Trontelj & Fišer, ), and additional analyses almost a decade later suggested that cryptic species actually may be heterogeneously distributed across animal phyla (Pérez‐Ponce de León & Poulin, ). The evidence for homogenous distribution of cryptic species across geographic regions is conflicting (Eme et al., ; Gill et al., ; Voda, Dapporto, Dinca, & Vila, ); perhaps an heterogeneous distribution can be detected only at global geographic scales.…”
Section: Cryptic Diversity In Biodiversity Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…ants: Pape 2016; diatoms: Falasco et al 2014;fungi and yeasts: Vanderwolf et al 2013;nematodes: Du Preez et al 2017;spiders: Mammola andIsaia 2017b, Mammola et al 2018a). Nonetheless, it has been recently shown that the existence of cryptic diversity does not always represent a major problem when investigating the ecological factors driving patterns of subterranean species richness (Eme et al 2018). Nonetheless, it has been recently shown that the existence of cryptic diversity does not always represent a major problem when investigating the ecological factors driving patterns of subterranean species richness (Eme et al 2018).…”
Section: Discussionmentioning
confidence: 99%